Avaliação da gestão e do gerenciamento dos resíduos sólidos têxteis numa fiação na cidade de Maringá - Paraná - Cardoso, Patrícia Mellero Machado (2012)
The accumulation of industrial solid wastes has been subject of great concern, because many industries do not provide proper treatment and disposal, causing environmental consequences and damages to public health. The textile industry is embedded in this problem because it produces large quantities of industrial solid wastes. This work is guided to an assessment of the current situation of solid wastes management of a mixed recycled polyester/cotton yarn P/C 50/50 production. For this purpose, an exploratory field research was conducted to diagnose the management and environmental management strategies adopted for the reduction of solid wastes generated in the production process chosen for the study case of the wiring. The methodology used for the diagnosis is implemented by observing the yarn industry in situ, in order to describe the production processes stages required to manufacture the recycled polyester / cotton yarn, and the sorts of solid wastes, to serve as primary data in the construction of flow diagrams and materials detailed process flow diagram. At the same time, the data on management strategies and the management of textile solid wastes wer collected through direct observation in the mixed yarn production process, questionnaires and interviews with those responsible for managing the wiring solid wastes, in order to figure out how to manage and which environmental management instruments would be adopted. By means of the diagnosis it was found that the solid wastes management is carried out efficiently and achieves the proposed goals by the wiring industry corresponding to the maximum recycling rate of the residues as raw material in the industry itself or in other wiring facilities for textile yarns production. It was found that the waste generated as powder filter has deficiencies in disposal. It was found that there was use of some environmental management strategies with focus on pollution prevention, such as the substitution of virgin raw materials by recycled ones, use of new technologies and automated machinery, as well as the use of operational improvements in the process. It is concluded that, although the management have some weak points, especially in solid wastes disposal, yet has good management and solid wastes management that ensures minimal losses in the textile production process for the mixed polyester/ cotton yarn.